2002
DOI: 10.1071/ar01023
|View full text |Cite
|
Sign up to set email alerts
|

Effects of water deficit on Mediterranean and temperate cultivars of tall fescue

Abstract: Two glasshouse experiments were carried out to evaluate the morphological and physiological responses to water deficit of Mediterranean and temperate tall fescue (Festuca arundinacea Schreb.) cultivars. In Expt 1, 3 cultivars were studied: 2 temperate cultivars, Grasslands Advance (GA) and El Palenque (EP); and a Mediterranean cultivar, Maris Kasba (MK). Water deficit was induced in containers of 4 plants of a single cultivar by withholding water. In Expt 2, plants of EP and MK were grown together in the same … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 52 publications
3
31
2
Order By: Relevance
“…Our results contrast with the work of Assuero et al (2002) who showed differences in water status between tall fescue cultivars, depending upon their origin. However, their trial was in a confined soil volume and could not account for the role of the deep root system of tall fescue in maintaining positive turgor and growth over dry periods (Garwood and Sinclair 1979;.…”
Section: Autumn Sowing and Dormancycontrasting
confidence: 86%
“…Our results contrast with the work of Assuero et al (2002) who showed differences in water status between tall fescue cultivars, depending upon their origin. However, their trial was in a confined soil volume and could not account for the role of the deep root system of tall fescue in maintaining positive turgor and growth over dry periods (Garwood and Sinclair 1979;.…”
Section: Autumn Sowing and Dormancycontrasting
confidence: 86%
“…Malinowski et al (2011) also observed that summer-dormant tall fescue was less competitive than continental tall fescue when both types were grown in binary mixtures with alfalfa, especially when constrained by low soil moisture availability in summer. Summer-dormant tall fescue may be able to coexist only with species expressing a similar growth pattern (Malinowski et al 2008) and may not be tolerant of a summer-active competitor (Assuero et al 2002). In non-native environments such as those of the Southern Great Plains, summer-dormant tall fescue is not expected to be able to take advantage of summer soil moisture, in contrast to native temperate and warm-season flora, because its growth pattern is highly restricted.…”
Section: Drought Tolerance-the Role Of Endophytesmentioning
confidence: 99%
“…Shade-grown tall fescue has fewer tillers plant -1 , lower specific leaf mass (SLM) and CO 2 exchange rate, and more leaf lamina air space than plants at high irradiance (Allard et al 1991a, b;Burner and MacKown 2006). Tall fescue responds to water stress by reducing plant size and growth rate, decreasing evaporative surface area, increasing root-shoot ratio, and reducing stomatal conductance (Assuero et al 2002).…”
Section: Introductionmentioning
confidence: 99%